2018
DOI: 10.14238/pi58.3.2018.138-45
|View full text |Cite
|
Sign up to set email alerts
|

Sitting height, sitting height/height ratio, arm span and arm span-height difference of healthy adolescents in Surakarta, Indonesia

Abstract: Background Sitting height, sitting height/height ratio (SHR), arm span, and arm span-height difference (AHD) are indices to diagnose conditions of disproportion. Reference data on sitting height, SHR, arm span, and AHD for Indonesian children are limited.Objective To compile reference data on sitting height, SHR, arm span, and AHD in Indonesian adolescents, and to compare these indices for boys and girls at various ages.Methods A population-based survey was conducted from August 2016 to November 2017 in three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Our previous study on the sitting height/height ratio in adolescents showed similar values between boys and girls. 8 The knee height of children with short stature was smaller than that of children with normal stature, but there were no differences in the patterns of knee height/height ratio with respect to stature in our subjects. The peak knee height/height ratios in children with short or normal stature were similar.…”
Section: Discussionmentioning
confidence: 44%
See 1 more Smart Citation
“…Our previous study on the sitting height/height ratio in adolescents showed similar values between boys and girls. 8 The knee height of children with short stature was smaller than that of children with normal stature, but there were no differences in the patterns of knee height/height ratio with respect to stature in our subjects. The peak knee height/height ratios in children with short or normal stature were similar.…”
Section: Discussionmentioning
confidence: 44%
“…These results were in agreement with those of our previous study on sitting height/height ratio and another study involving an Asian population with similar proportions. 8,9 There were some limitations to our study. Since we conducted a study of urban schoolchildren from one elementary and one junior high school in Surakarta, Central Java, our sample might not be representative of all schoolchildren in Indonesia.…”
Section: Discussionmentioning
confidence: 96%